Understanding Population Dynamics” in Shaping the Bottom Line- Is Demography the Destiny - Dissanayake, Lakshman (My University, 2014)
This paper examines fertility change, population momentum and age structure of the population in Sri Lanka with some new findings on the Second Demographic Dividend. These aspects are of interested to the business sector in Sri Lanka because peoples’ needs and requirements depend on their age and gender; consumer behaviour is greatly determined by age and gender of consumers; and use of accurate information and understanding of changing demography is essential for business development. Most importantly, these dynamics favour the country’s development process. The paper reveals that the tendency for population growth to continue beyond the time that replacement-level fertility has been achieved because of the relatively high concentration of women in the childbearing years. It further shows that recent fertility increase will extend the population growth momentum further. This can extend the terminal year (beyond 2037) of the first demographic dividend too. Such change will be beneficial to the country’s development if appropriate policies are in place. The paper also claims that the second demographic dividend operates in two ways: Greater Accumulation of Wealth. Lower fertility and increased life expectancy generally lead to greater wealth: First, people accumulate wealth during their working years, and by the time they reach old age their wealth is at or near its peak and Second, as people realize they will live longer, they will be more motivated to accumulate wealth that they can use to support themselves in old age. As people’s wealth increases, they are more likely to invest in the health and education of each of their children. With fewer children to care for, it is possible for parents to invest more resources in each child. The paper argues that if economic policies and financial mechanisms are put in place early in the process of population aging to help workers accumulate assets—such as property, funded pensions, and personal savings—they can achieve more financial independence in old age and depend less on government and their families. In this scenario, population aging will lead to sustainable family and government support systems and boost capital, productivity, and per capita income.
Keywords: Understanding Population Dynamics” in Shaping the Bottom Line- Is Demography the Destiny